The Clinical Relevance of Noncriteria Antiphospholipid Antibodies - Bertolaccini, Maria Laura; Sanna, Giovanni (Seminars in Thrombosis and Hemostasis, 2018)
While lupus anticoagulant (LA), anticardiolipin antibodies (aCL), anti-β2 glycoprotein I (anti-β2GPI) antibodies represent the best available and the most widely used tests in the investigation for antiphospholipid syndrome (APS), evidence gathered in recent years indicates that other antiphospholipid antibodies (aPL) specificities may also play a role in the syndrome. Several autoantibodies have been shown to be complexed with phospholipids other than cardiolipin, or to some domains of β2GPI, or else directed to other proteins of the coagulation cascade, and these have also been proposed to be of relevance to APS, and their diagnostic value and clinical utility are the focus of current research.
Keywords: prothrombin; coagulation; phosphatidylserine; lupus; thrombotic risk; β2GPI